Stratigraphy and structural position of the type locality of the Phasoula Formation (Upper Triassic, southwestern Cyprus) - Bragin Nikita; Bragina Liubov; Tsiolakis Efthymios; Symeou Vasilis; Papadimitriou Nikolas (Geološki Anali Balkanskoga Poluostrva)
The Upper Triassic Phasoula Formation in its type locality in Dhiarizos River valley is interpreted as a large tectonic block incorporated in the Upper Cretaceous Mamonia Mélange. Volcanics of the Phasoula Formation are dated as Upper Triassic based on radiolarian assemblages from chert intercalations within these volcanics, while the clayey matrix of the mélange yields small blocks of red radiolarian cherts which are dated by radiolarians as Cenomanian. According to biostratigraphic and structural data all major localities of the Phasoula Formation (Petra tou Romiou, Akamas, Ayia Varvara, Phasoula) represent large blocks within the Mamonia Mélange.